Hybrid nanofibrous mats as ionic liquid host for electrolytes - Ho, Shu Wei (2015)
In this study, highly ionic conductive polymer electrolytes were prepared using electrospun nanofibrous poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) mats as host for 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM-BF4), a common ionic liquid. The PVDF-HFP mats were modified with ceramic nanoparticles to increase ionic liquid uptake and thus improve ionic conductivity. Two different types of nanoparticles, alumina Al2O3 and silica SiO2, were synthesized to make two types of modified mats which were characterized by using FE-SEM, raman spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR) and impedance spectroscopy. The results showed that there was a significant increase in conductivity for the modified mats from the unmodified one, which was mainly due to the presence of a higher amount of free ionic liquid ions in the fiber network of the mats.